2014
DOI: 10.4269/ajtmh.14-0068
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus and Hepatitis C Virus Infections in United States-Bound Refugees from Asia and Africa

Abstract: Abstract. The aim of this study was to determine the prevalence of active hepatitis B and C virus infections among refugees from various countries in Africa and Asia. Pre-admission serum samples collected during 2002-2007 from refugees originating from Bhutan (N = 755), Myanmar (N = 1076), Iraq (N = 1137), Laos (N = 593), Thailand (N = 622), and Somalia (N = 707) were tested for hepatitis B virus (HBV) DNA and hepatitis C virus (HCV) RNA. The HBV DNA (genotypes A, B, C, and G) was detected in 12.1% of samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 28 publications
5
38
0
1
Order By: Relevance
“…Samples positive for HBsAg were tested for HBV DNA by in-house quantitative PCR assays as previously described in Ref. [8]. Briefly, total nucleic acids (TNA) were extracted using 200 µL of serum with the Roche MagNA Pure Isolation Kit I (Roche Applied Science, Rochester, NY) with a final elution volume of 50 µL followed by Taqman quantitative PCR (qPCR) for HBV DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Samples positive for HBsAg were tested for HBV DNA by in-house quantitative PCR assays as previously described in Ref. [8]. Briefly, total nucleic acids (TNA) were extracted using 200 µL of serum with the Roche MagNA Pure Isolation Kit I (Roche Applied Science, Rochester, NY) with a final elution volume of 50 µL followed by Taqman quantitative PCR (qPCR) for HBV DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Myanmar genotype C has been identified as the predominant genotype, both amongst local residents and those migrating from Myanmar. 8,15,16 Genotype C is associated with a later seroconversion from Hepatitis B e-Antigen (HBeAg) positive status to HBeAg negative, anti-HBe positivity and more advanced liver disease. 17 Other studies however, have focused on populations such as from Korea with largely genotype C2, and it is unknown if this is also the case with genotype C1.…”
Section: Withinmentioning
confidence: 99%
“…Within Myanmar genotype C has been identified as the predominant genotype, both amongst local residents and those migrating from Myanmar . Genotype C is associated with a later seroconversion from Hepatitis B e‐Antigen (HBeAg) positive status to HBeAg negative, anti‐HBe positivity and more advanced liver disease .…”
Section: Introductionmentioning
confidence: 99%
“…In a study looking at the prevalence of active hepatitis C virus infections among refugees in the United States of America from various countries in Africa and Asia, it was reported that 63 out of a total of 4890 (1.1%) were positive for HCV RNA. The refugees from Thailand had greater numbers of HCV-positive samples than refugees from other countries [19]. In Lebanon, among the Syrian refugees, the number of reported cases of Hepatitis C doubled from a total of four cases in 2013 to eight cases in 2016 [18], a trend similar to hepatitis B.…”
Section: Hepatitis Cmentioning
confidence: 85%